2015
DOI: 10.2967/jnumed.114.141432
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy and Sentinel Nodes

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to describe (1) generic fundamentals of lymphoscintigraphy procedures of sentinel lymph node biopsy (SLNB) protocols; (2) specific injection and imaging components of SLNB protocols used in the management of patients with breast cancer, melanoma, and head and neck malignancies; and (3) specific indications of breast cancer, melanoma, and head and neck malignancies that suggest inclusion of a SLNB in the management of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 64 publications
(72 reference statements)
2
40
0
2
Order By: Relevance
“…Therefore, detecting and assessing the sentinel lymph node (SLN), which is the first lymph node to which cancer cells drain from a primary tumor, is crucial. To identify the SLN, researchers have explored numerous biomedical imaging techniques . Classically, lymphoscintigraphy with radiocolloid injection has been widely used for preoperative lymph node imaging, but its imaging resolution is relatively low .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detecting and assessing the sentinel lymph node (SLN), which is the first lymph node to which cancer cells drain from a primary tumor, is crucial. To identify the SLN, researchers have explored numerous biomedical imaging techniques . Classically, lymphoscintigraphy with radiocolloid injection has been widely used for preoperative lymph node imaging, but its imaging resolution is relatively low .…”
Section: Introductionmentioning
confidence: 99%
“…A specific lymphoscintigraphy pharmaceutical, 99m Tc-tilmanocept, was approved by the U.S. FDA for SLN protocols for patients with breast cancer and melanoma in 2013 and for patients with head and neck squamous cell carcinoma in 2014 [18]. 99m Tc-tilmanocept is a receptor-based radiotracer that can specifically bind to mannose receptors (CD206), which are found in high concentrations on the surface of macrophages and dendritic cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, data demonstrated that SPECT/CT can be useful in several situations: 1) if SLN is not detected; 2) if extra-axillary lymph nodes are detected; 3) if an internal mammary lymph node is detected; 4) if a contamination is suspected; or 5) if a patient has a high body mass index, has undergone previous breast surgery, or has contralateral uptake [18, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of lymphoscintigraphy is to identify and localize all sentinel lymph nodes(SLNs) for surgical biopsy (34). The SLN is the first lymph node receiving drainage from the primary tumor.…”
Section: Lymphoscintigraphymentioning
confidence: 99%